Targeted Metabolomics for Homocysteine-Related Metabolites in Primary Hepatocytes - Selicharová, Irena; Kořínek, Marek (Methods in molecular biology (Clifton, N.J.), 2015)
Liquid chromatography-tandem mass spectrometry has become the most convenient method to identify and quantify low molecular weight metabolites from various sources. Metabolomics studies of hepatocytes hold promise for the identification of the mechanisms of toxicant-related disease processes. In this chapter, we present a rapid and sensitive liquid chromatography-tandem mass spectrometry method for the quantification of intracellular concentrations of nine homocysteine-based metabolites, namely homocysteine, methionine, cysteine, dimethylglycine, cystathionine, S-adenosylmethionine, S-adenosylhomocysteine, choline, and betaine. The method is specifically designed for the analysis of cultured primary hepatocytes.
Keywords: hepatocyty; hmotnostní spektrometrie; Hepatocytes; Mass Spectrometry; Homocysteine; homocystein; metabolomika; lidé; primární buněčná kultura; Metabolome; metabolom; Chromatography, Liquid; Metabolomics; chromatografie kapalinová; Primary Cell Culture; Humans